If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2(3x + -5) = 5x + 14 + -7x Reorder the terms: 4x + 2(-5 + 3x) = 5x + 14 + -7x 4x + (-5 * 2 + 3x * 2) = 5x + 14 + -7x 4x + (-10 + 6x) = 5x + 14 + -7x Reorder the terms: -10 + 4x + 6x = 5x + 14 + -7x Combine like terms: 4x + 6x = 10x -10 + 10x = 5x + 14 + -7x Reorder the terms: -10 + 10x = 14 + 5x + -7x Combine like terms: 5x + -7x = -2x -10 + 10x = 14 + -2x Solving -10 + 10x = 14 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -10 + 10x + 2x = 14 + -2x + 2x Combine like terms: 10x + 2x = 12x -10 + 12x = 14 + -2x + 2x Combine like terms: -2x + 2x = 0 -10 + 12x = 14 + 0 -10 + 12x = 14 Add '10' to each side of the equation. -10 + 10 + 12x = 14 + 10 Combine like terms: -10 + 10 = 0 0 + 12x = 14 + 10 12x = 14 + 10 Combine like terms: 14 + 10 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| X-3=25-10 | | 3xy+x+y=0 | | 441.5+x=22 | | u+4.6=9.17 | | h=x^2-8ln-2 | | tan(2pi+x)= | | h(x)=x^2-8ln-2 | | 8x+19=-28-8x | | -2w+8=-56 | | 5p^2+6p+1=O | | (y+9)2*2-(y+5)2*2=28 | | -7u-46=31 | | h(t)=-16t^2+36t+5 | | Y-8=2/3x | | 6d+57=39 | | 2x+3=2x-(3x+2x)+6 | | -6(-4x+3)-5x=7(x-2)-1 | | -5a+(-18)=22 | | -2(3+x)+3(2+2x)=1+4x | | 10x-3y-5x+13y= | | 10xsquare-3x-1=0 | | 2p-(-86)=52 | | 3600=200x-x^2 | | -4l+(-25)=55 | | 3x-13y=2forwhy | | 4(x-2)+2x=3(x-1)-11 | | -3e-72=-18 | | -214+-8(2x-3)=-334 | | 3v-36=-42 | | 10x+5=12y+5 | | 15y+20= | | 4r+(-12)=48 |